Characteristics of Oil Used in Frying Peanuts, Cassava And Mackarel Tuna - Aprialis Aprialis; Anwar Kasim; Rini Rini (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2021)
The characteristics of used frying oil that are carried out repeatedly using high temperatures and with various types of frying materials will produce new types of oil characteristics, either the appearance and disappearance of certain types of chemical components or changes in the physical properties of frying oil. This study aims to determine the characteristics of cooking oil used in frying peanuts which have high fat content, high carbohydrate content of cassava and mackarel tuna which have high protein content. Samples of used oil were obtained from the use of pure oil from palm oil and then the 3 different types of material were fried with 10 frying repetitions. The used frying oil was then visually observed and analyzed for the number of peroxides, free fatty acids, and moisture content, color test, amount of oil lost and its fatty acid profile. In addition, the amount of oil lost due to frying was observed. The results of the observation of physical properties showed that the smell of oil became rancid, the taste of the oil became bitter and the color turned black. The results of chemical analysis showed that the highest peroxide number was 50 meq / kg, the highest ALB was 4.35%, and the highest moisture content was 3.21% , the oil color changed to brown to black, the highest amount of oil lost due to frying was cassava frying oil. namely 58.4% , . The fatty acid profile of used frying oil has been obtained and there is a decrease in the percentage, the appearance of stearic acid and the loss of heptadecanoic fatty acids in the used cooking oil for peanuts, cassava and mackarel tuna.